Twentieth-Century Italian Literature in English Translation : An Annotated Bibliography, 1929-1997 - Healey, Robin, 1942- (Book collections on Project MUSE., 1998)
This bibliography lists English-language translations of twentieth-century Italian literature published chiefly in book form between 1929 and 1997, encompassing fiction, poetry, plays, screenplays, librettos, journals and diaries, and correspondence.